Risk management and financial derivatives : a guide to the mathematics (Basingstoke : Macmillan, 1997)
This book is divided into six parts: Introduction; Interest rates and yield curves; Derivative pricing; Investment management; Risk management; and Mathematical techniques.
Keywords: Economics; Derivative securities -- Mathematics; Risk management -- Mathematics